Collectives' and individuals' obligations: a parity argument. Issue 1 (2nd January 2016) - Collins, Stephanie; Lawford-Smith, Holly
Abstract: Individuals have various kinds of obligations: keep promises, don't cause harm, return benefits received from injustices, be partial to loved ones, help the needy and so on. How does this work for group agents? There are two questions here. The first is whether groups can bear the same kinds of obligations as individuals. The second is whether groups' pro tanto obligations plug into what they all-things-considered ought to do to the same degree that individuals' pro tanto obligations plug into what they all-things-considered ought to do. We argue for parity on both counts.